The present perfect and preterite in British and American English - Žetko, Katarina Dea (ELOPE (Ljubljana), 2010)
The objective of our article is to present the selected results of the research which was conducted for the purpose of our master's thesis. We focused on the transfer of the functions of the present perfect into the domain of the preterite in informal British and American English. We put together a British and an American corpus and analysed the differences and similarities between British and American English in this transfer. We examined some factors that may influence this transfer either in American or British English, or in both varieties. The major factors will be presented in this article. The results show that the differences between both varieties mostly occur in the frequency of this transfer. Moreover, in American English there are more significant factors than in British English. Nevertheless, we can observe that the general tendency is the same in both varieties. This fact may indicate that this phenomenon, which was first noticed in informal American English, is spreading to informal British English.
Keywords: American English; ameriška angleščina; angleščina; britanska angleščina; British English; colloquial language; English language; jezikovne zvrsti; pogovorni jezik; present perfect; preteklik; preterite; sedanjik; slovnični časi; Tenses